2007
DOI: 10.1079/pavsnnr20061065
|View full text |Cite
|
Sign up to set email alerts
|

Modifying forestry and agroforestry to increase water productivity in the semi-arid tropics.

Abstract: The need to increase water productivity is a growing global concern as the World Commission on Water has estimated that demand for water will increase by c. 50% over the next 30 years and approximately half of the world's population will experience conditions of severe water stress by 2025. Three-quarters of African countries are expected to experience unstable water supplies, whereby small decreases in rainfall induce much larger reductions in streamflow. Vital water catchments have been lost or are being deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
(100 reference statements)
0
25
0
Order By: Relevance
“…2002, 2006, 2007Bayala et al 2008). In semi-arid Kenya, Jackson et al were not pruned to maximise woody biomass production and reflect the objectives of subsistence farmers.…”
Section: Wwwspringerlinkcommentioning
confidence: 99%
See 2 more Smart Citations
“…2002, 2006, 2007Bayala et al 2008). In semi-arid Kenya, Jackson et al were not pruned to maximise woody biomass production and reflect the objectives of subsistence farmers.…”
Section: Wwwspringerlinkcommentioning
confidence: 99%
“…However, agroforestry does not always provide a solution, as negative interactions may occur due to competition with adjacent crops (Ong et al 2006(Ong et al , 2007Sun et al 2008). Some reports suggest there is little competition on bench terraces due to spatial or temporal separation of the trees and crops (Cooper et al 1996), although farmers have reported that trees may compete with adjacent crops (Wajja-Musukwe et al 1997;Sun et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Improved fallowing is one of many technologies which are currently being used for soil fertility improvement in low input agricultural systems in the semi arid to arid tropics (Kwesiga et al 1999;Mafongoya et al 2006). Improved fallows have been adopted by farmers Southern Africa in countries such as Zambia, Malawi (Kwesiga et al 1999;Mafongoya et al 2006), semi arid Kenya (Ong et al 2006(Ong et al , 2007 and in humid tropics (Siriri et al 2010). Improved fallows can increase nutrient input through nitrogen fixation (Sun et al 2008;Mafongoya and Dzowela 1999;Chikowo et al 2004;Mapfumo et al 2005;Jose et al 2004), they built up of soil organic matter (Nyamadzawo et al 2008b;Lal 1989;Kwesiga and Beniest 1998) and they improve infiltration rates of soils (Young 1997;Nyamadzawo et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Reductions in soil evaporation can be effective in reducing crop transpiration rates that result in an increased water use efficiency Ong et al, 2006;Lott et al, 2009). Shading also reduces leaf temperature, minimising heat stress, reducing air temperature, wind speed, and saturation deficit, effectively reducing water use (Monteith et al, 1991;Jonsson et al, 1999;Ong et al, 2000).…”
Section: Planting Densitymentioning
confidence: 99%